Dietary copper intake and risk of myocardial infarction in US adults: A propensity score-matched analysis - Wen, He; Niu, Xiaona; Hu, Lang; Sun, Nan; Zhao, Ran; Wang, Qiuhe; Li, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objectives Most studies have examined the association between serum copper and myocardial infarction, but there is little evidence of the association between dietary copper intake and myocardial infarction. Materials and methods The study included a total of 14,876 participants from the 2011 to 2018 National Health and Nutrition Examination Survey (NHANES). Multivariate logistic regression model was used to analyze the association between dietary copper intake and the risk of myocardial infarction. To reduce selection bias, we use nearest neighbor propensity score matching (PSM) in a 1:2 ratio. Restricted cubic spline (RCS) method is used to study the non-linear relationship. Subgroup stratification was used to further investigate the association between copper intake and myocardial infarction. Results The median dietary copper intake was 1.0825 mg/day. A myocardial infarction had occurred in approximately 4.4% (655) of the participants. Before and after matching, multivariate logistic regression models revealed a negative correlation between dietary copper intake and the risk of myocardial infarction. The higher quartile of subjects had a noticeably lower risk of myocardial infarction in comparison to those in the first quartile of copper intake. According to RCS findings, dietary copper intake and myocardial infarction have a non-linear and dose-response relationship. According to stratified analysis, the dietary copper intake was a substantial protective element for those who were ≥ 50 years old, female, 25 ≤BMI <30, with history of smoking, hypertension, diabetes and ortholiposis. Conclusion Increased dietary copper intake was associated with a lower risk of myocardial infarction. It is especially significant in elderly-aged women, overweight individuals, smokers, hypertension, and diabetic patients.